Custo de bem-estar da violência letal no Brasil e desigualdades regionais, educacionais e de gênero - Daniel Ricardo de Castro Cerqueira; Rodrigo R. Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– In this paper we estimate the welfare cost of lethal violence in Brazil and analyze the impact of regional, educational, and gender heterogeneities. In the adopted approach, which is based on Rosen (1988) and Soares (2006), we calculate the marginal willingness to pay to avoid the risk of premature death due to violence. The results, derived from information on the characteristics of each individual killed and on socioeconomic and demographic data, indicate that the welfare cost of lethal violence is the equivalent of 78% of GDP or 2.3% of GDP per annum. Our analysis also indicated that reliance on aggregate data to perform such calculations, without taking into account the different types of heterogeneity mentioned, can lead to a bias of up to 40% of the value that would be obtained were those socioeconomic differences considered.
Keywords: K42; J17; 330